C-myc amplification in precancerous lesions of oral cavity and larynx - Ninković Tanja; Dedović Nasta; Kosanović Rade; Dimitrijević Bogomir; Josipović Obrad; Vukadinović Miroslav; Milašin Jelena (Serbian Medical Society - Dental Section, Belgrade, 2003)
Although myc genes are an important family of oncogenes involved in human carcinogenesis, data concerning its role in head and neck tumors are quite limited. Moreover, information regarding precancerous lesions is almost inexisting. In order to better understand mechanisms of progression of premalignant lesions into malignant and the possible role of c-myc amplification, the status of this oncogene was analyzed in two types of pathological changes known to possess malignant transformation potential oral leukoplakia and chronic laryngitis. In the first type of lesions a high percentage of c-myc activation (33%) was observed pointing to a probable role of myc in leukoplakia malignant transformation, while in the other type of lesion there were no signs of myc amplification.